Effects of acidified fermentation by-products and prepartum DCAD on feed intake, performance, and health of transition dairy cows - Bradford, Barry J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two commercially available acidified fermentation by-products were evaluated in the close-up period (21 days before expected calving) for their effects on feed intake, postpartum performance, and cow health. Diets were formulated to contain similar protein and energy values but differed in dietary cation anion difference and anion source. Treatments were Bio-Chlor, SoyChlor, and a control. Prepartum feed intake tended to be lower for SoyChlor than for the control, but postpartum intake did not differ among dietary treatment groups. Likewise, no significant differences were detected for milk yield between treatments. Protein percentage, milk urea nitrogen, and lactose percentage were greatest for SoyChlor-treated cows. Therefore, despite a trend for a negative effect on prepartum feed intake, SoyChlor supported similar productivity in early lactation.
Dairy Research, 2009 is known as Dairy Day, 2009
Keywords: Dairy; By-products; Dietary cations; Dietary anions; Feed intake